Biofuel as a Renewable Energy: Potential, Technology, and Challenges Towards a Sustainable Energy Transition - Sandi, Dianisa Khoirum; Atyanta, Ariefanda Irza; Fifalah, Maisa Linta; Rizqi, Fika Ariza (Politeknik Negeri Semarang, 2025)
Biofuel is a promising renewable energy alternative to reduce dependence on fossil fuels and lower greenhouse gas emissions. This article presents a comprehensive overview of biofuel classification (generation I–IV and physical forms), production technologies (fermentation, transesterification, gasification, pyrolysis), and the applications of bioethanol, biodiesel, and biogas in the transportation, industrial, and power generation sectors. Energy efficiency and environmental impact analyses are conducted using a life cycle assessment (LCA) approach, while national energy policies are examined in the Indonesian context, including the mandatory blending program (B30–B50) and sustainability strategies. While biofuels have significant potential, challenges such as production efficiency, land conflicts, and regulatory consistency need to be addressed for biofuels to truly contribute to the national energy transition